Civic Engagement in Nursing: Measuring Participation, Reflecting on Influences, and Harnessing Momentum. Issue 3 (3rd July 2021) - Rewakowski, Carrie; Atav, Serdar; Clancy, Helen; MacPherson, Maria
ABSTRACT: This study explored civic engagement and related variables among registered nurses and non-nurses. Historical influences that have shifted engagement are discussed. This was a cross-sectional, observational study. Data was collected in a convenience sample (n = 727) of registered nurses (n = 232) and non-nurses (n = 495) and was analyzed using descriptive and ANOVA statistics. Nurses were more engaged than non-nurses ( p = .000). Age, education, and field of practice were significant variables among nurses. Nurses are positioned to answer the call to civically engage for health-related issues. Findings underscore ways to elevate and harness civic engagement among nurses.